Reliability Assessment of Damaged RC Moment-Resisting Frame against Progressive Collapse under Dynamic Loading Conditions. Issue 2 (February 2014) - Huang, Zhiwei; Li, Bing; Sengupta, Piyali
Reinforced concrete (RC) structures when subjected to sudden destruction of a column by blast pressure, experience dynamic effects in its response. Hence, reliability assessment of the damaged ductile frame against progressive collapse under dynamic loading conditions is conducted in this research. This paper aims at establishing three performance functions, two of which will consider structural collapse due to lack of strength and deformation capacity respectively while the third will incorporate the shear response of structural components for the weakest collapse mechanism. Since any of the performance functions may lead to structural collapse, a global performance function of the damaged structure is developed by considering the minimum of the functions. The results are then used in conjunction with Monte Carlo Simulation (MCS) to estimate the reliability of the damaged structure. A numerical example of a four storey RC frame is presented to address the applicability of the proposed approach and the effects of different structural parameters on its reliability against progressive collapse after the sudden column loss are investigated thereafter.